Chemical composition and in situ ruminal degradability of dry matter in mixed silages of Tithonia diversifolia: Pennisetum purpureum cv. Cuba CT-169, inoculated with VITAFERT - Gutiérrez, Delfín; Morales, A.; Elías, A.; García López, R.; Sarduy, Lucía (Cuban Journal of Agricultural Science, 2016)
The chemical composition and in situ ruminal degradability of dry matter in mixed silages was analyzed, using different proportions of Tithonia diversifolia and Pennisetum purpureum cv. Cuba CT-169, inoculated with VITAFERT. A completely randomized design was used, with a 4 x 4 factorial arrangement. Treatments consisted on replacing four levels of P. purpureum with T. diversifolia (20:80, 40:60, 60:40 and 80:20 % weight HB), with the proportional inclusion of four levels of VITAFERT (0; 4.5; 6.0; 8.0 % weight HB) in the mixture. At the end of fermentation period (62 d), the chemical composition (% DM, % CP, % ash, % NDF) and in situ ruminal degradability of dry matter were determined. For that purpose, two bovine females (Holstein x Zebu) were used, with 475 kg of mean liveweight, with a fistula in the rumen and fed ad libitum with grass forage and a commercial concentrate at a rate of 6 g. kg LW-1. The bags were incubated during a dynamics of fermentation (8, 16, 24, 48, 72 and 96 h). The results showed an increase in the content of CP and ash, and a reduction of NDF in all the mixtures inoculated with VITAFERT. However, the levels 4.5 and 6.0 % of VITAFERT reached the best response. The combination of 20:80 Tithonia:Pennisetum with 4.5 % of VITAFERT in the mixture had the highest degradability(48 %) in less time (30 h), degradation speed (c=13 % h-1) and effective degradability (EDk0.02= 42.49 % , k0.04= 38.32 %). Key words: Tithonia, silages, effective degradability, proportions